Modulation of total electron content by ULF Pc5 waves. Issue 6 (2nd June 2014) - Pilipenko, V.; Belakhovsky, V.; Murr, D.; Fedorov, E.; Engebretson, M.
Abstract: An intriguing effect was found while analyzing the small‐scale variations of total electron content (TEC) derived from global positioning system (GPS) signals. We found a response in TEC variations to intense global Pc5 pulsations with periods of a few millihertz covering the corrected geomagnetic latitudes 58°–75° during the recovery phase of the strong magnetic storms on 31 October 2003. Earlier studies demonstrated that the GPS‐TEC technique is a powerful method to study the propagation pattern of transient disturbances in the ionosphere, generated by seismic or internal gravity waves. This technique has turned out to be sensitive enough to ULF waves as well. During periods with intense Pc5 geomagnetic wave activity, distinct pulsations with the same periodicity were found in the TEC data from high‐latitude GPS receiving stations in Scandinavia. Wavelet and cross‐spectral analysis showed a high coherence ( 0.9) between the periodic geomagnetic and TEC variations. Moreover, the relative amplitude of TEC periodic fluctuations ΔTEC/TEC was about or even larger than the relative amplitude of geomagnetic variations Δ B / B . So far, the effect of TEC modulation by Pc5 waves is not well understood and is still a challenge for the MHD wave theory. Various possible modulation mechanisms have been estimated, but no mechanism has been firmly identified. Key Points: Global Pc5 pulsations modulate the total electron content Relative amplitudes of TEC and geomagnetic fluctuations is about the same